Arthrogrypotic Club Foot - Al-Mihyawi, Abdullah Y (AL-Kindy College Medical Journal, 2007)
Background: Arthrogryposis Multiplex congenita is arare disorder, characterized by multiple joint deformitiesi.e. multiple congenital contractures, with shapelesslycylindrical limbs and absent skin creases.Club foot can be the only obvious deformity of thiswidespread disorder.Objective: To assess the most frequent recurrentdeformity after extensive soft-tissue release operations forarthrogrypotic club foot and its appropriate treatmentregarding combined tendon transfer and bony operations.Methods: A retrospective study of 14 patients witharthrogrypotic club foot (28 feet), had been operated on bymultiple soft tissue and bony operations and followed in aperiod between January (1993) till February (1999).Both clinical assessment including goniometer use tomeasure the recurrent deformity, and radiologicalassessment, was used in this study.Results: In this series, 4 patients (7 feet) had recurrentdeformity, 3 patients(5 feet) out of these 4 had recurrent forefoot adduction, 2of them had bilateral affection. The 4th patient hadbilateral recurrent varus heel.Conclusion: The main problem in arthrogrypotic clubfoot is the liability for recurrence. The most frequentrecurrent deformity was forefoot adduction. Combinedtendon transfer and bony operations can correct thedeformity once performed at the same cession forefootadduction. All required 2nd operation, in the 1st 3 patientcombined Evan’s (calcaneocuboid wedge-excision) andtibialis anterior transfer operations were performed.Talectomy was performed on one foot in the 4th patient,combined with capsulectomy of the calcaneocuboid joint,while triple arthrodesis don on the other foot